Self-Regulated Strategy Development to Teach Mathematics Problem Solving. (January 2020) - Popham, Michelle; Adams, Simone; Hodge, Janie
Many secondary students with specific learning disabilities (SLD) struggle with mathematics problem solving. When students with SLD are taught to use effective problem-solving strategies, their ability to solve mathematics word problems improves. The purpose of this article is to provide a guide for secondary teachers to implement self-regulated strategy development (SRSD) to teach mathematics problem-solving strategies to secondary students with SLD. The specific problem-solving strategy described in this article is SOLVE, which stands for Study the problem, Organize the facts, Line up a plan, Verify your plan with action, and Evaluate your results. Both SRSD and SOLVE are described, and an example of one teacher's application of SRSD is shared. When taught concurrently, SRSD and SOLVE can be useful tools to help students with disabilities overcome the challenges of problem-solving in mathematics.